Tailoring the synergistic dual-decoration of (Cu–Co) transition metal auxiliaries in Fe-oxide/zeolite composite catalyst for the direct conversion of syngas to aromatics. Issue 24 (15th November 2021) - Nawaz, Muhammad Asif; Saif, Maria; Li, Minzhe; Song, Guiyao; Zihao, Wang; Liu, Dianhua
Abstract : Tailoring the crystal lattice and multiple phase interfaces via the feasible accommodation of Cu–Co into the host (Fe) structure, expedited the surface oxygen vacancies that modulated the reduction/chemisorption behavior of active Fe species. Abstract : A one-step process for the conversion of syngas to aromatics (STA) has become an alternative key technology for non-petroleum carbon resources in the growing demand of the modern petrochemical sector. In the current study, the influence of various compositions of Cu and Co species in Fe–Co/Fe–Cu bimetallic systems were evaluated for the catalytic activity of integrated Fe-based/HZSM-5 catalyst in the STA process. It was demonstrated that the effective co-doping of Cu and Co metal species under adequate calcination temperature could feasibly accommodate the foreign elements into the host (Fe) structure. The crystal plane engineering, tailored lattice distortion, and generation of multiple-phase interfaces expedited the formation of abundant surface oxygen vacancies. The fabrication of highly-tuned CoFe2 O4 bimetallic nanocrystals worked towards the enrichment of the adsorption capabilities of the catalytic surface that could eventually dictate the reduction behavior of different (Fe, Cu, Co) metal oxides. The originated synergistic interactions of Cu–Co, higher concentration of generated oxygen vacancies, triggered the chemisorption of CO and increased dissociation of CO2 molecule during the reaction significantly provoked the intrinsic catalytic behavior. The fabricated catalytic system with the higher Fe5 C2 content and stronger basic sites drastically suppressed the overall gaseous phase (especially CO2 ∼22%), while exploiting ∼53% of the aromatics fraction in a stable CO conversion of 97%. This work manifests the synergistic interplay of Cu–Co dual-decorated metal auxiliaries for regulating the electronic configuration of iron oxide in the composite catalyst for the STA process.